Logarithmic type Direct and Synthetic Estimators using Bivariate Auxiliary Information with an Application to Real Data - Shashi Bhushan; Anoop Kumar; Rohini Pokhrel (Journal of the Indian Society of Agricultural Statistics, 2025)
This research work addresses bivariate auxiliary information-based logarithmic type direct and synthetic estimators for domain means in simple random sampling (SRS). The mean square error (MSE) of the suggested estimators is obtained, approximately to the first order. The efficiency standards by which the superiority of the suggested estimators is asserted are established. To demonstrate the superiority of the suggested estimators, a simulation investigation employing an artificially constructed normal population through the R programming language is also conducted. The analysis of real data from Swedish municipalities and the paddy crop acreage in the Mohanlal Ganj tehsil, Uttar Pradesh, India, also provides some applicability for the suggested estimators.